O inominável na experiência de linguagem de Marguerite Duras - Zanello, Valeska (2003)
Heidegger, in his most radical work, “Unterwegs zur Sprache”, pointed out the role of the unnamable in the poetic performance as possibilibity of experiencing speech. In this sense, it would be in the lack of words that the dimension of the word as restorer of being and the world becomes more evident. This article aims to discuss how the experience of the unnamable, present as existential pain in Marguerite Duras’s writings, opens up the possibility of forming a fertile soil for the occurrence of that experience.